A cross-sectional audit of the prevalence of stunting in children attending a regional paediatric cardiology service. (11th September 2015) - Marino, Luise V.; Magee, Alan
Abstract: CHD is associated with poor growth, delayed motor and language skills development, and increased length of hospital stay; 28.2% of infants were stunted, with z-scores<−2. The severity of surgery score was not associated with an increased length of stay, suggesting that a low weight-for-age z-score at the time of surgery may impact on length of stay.